Multi-objective Design Optimization of Structural Geometric Nonlinearities for Response Attenuation of VLBI Antennae Subject to Aerodynamic Turbulence - Parsons, William P.; Gasparetto, Victor E. L.; ElSayed, Mostafa S. A.; Saad, Mohamed; Shield, Stephen; Brown, Gary L.; Hilliard, Lawrence M. (Journal of Vibration Engineering & Technologies, 2023)
Background Very-long-baseline interferometry (VLBI) is a technique employed in radio astronomy where a signal from a planetary radio source is collected on earth at multiple radio antennae. Working in a network, the time difference of the radio signal reception by the antennae is employed to achieve an effective aperture allowing for the development of a significantly high-resolution images of the space. However, the signal clarity of each individual antenna is dependent on its structural response under environmental conditions. This paper proposes a design optimization framework for VLBI antennae for their performance maximization under aerodynamic gust employing structural geometric nonlinearities. Purpose The dynamic aeroelastic response of the antenna is attenuated by optimizing actuation length changes in active structural elements to improve the pointing accuracy of the VLBI antenna under wind gust loads. No framework currently exists in the open literature that leverages the principles of tensegrity structures for vibration attenuation of VLBI antenna using control actuations, therefore, the need for such a framework has been established to design high-performance VLBI ground stations. Methods Dynamic aeroelastic gust analysis is performed considering the Power Spectral Density (PSD) with the Davenport spectrum (DS) statistical model and Tuned Discrete Gust analysis with a One-Minus Cosine gust profile. Analyses are performed for two different operating conditions using time-consistent loads (TCL) and time-consistent displacements (TCD). Additionally, the effect of a varying number of active elements for control actuations is analyzed in the boomarm subsystem of the VLBI antenna while minimizing both the pointing error and total strain energy using an optimization framework employing a Multi-Objective Genetic Algorithm (MOGA). Results A case study was presented to showcase the proposed framework. A reduction of 82.6% with a total strain energy increase of 292.5% was obtained for the primary operating case under PSD gust excitation. On the other hand, at the increased mean wind speeds of the secondary operating case, the developed design algorithm was able to reduce the total pointing error by 80.9% but with a total strain energy increase of 825.3%. Similarly, for TDG analysis with the OMC excitation profile the optimization algorithm reduced the total pointing error by 51.6% with a TSE increase of 2098.1% and 80.5% with a TSE increase of 48.7% for the primary and secondary operating conditions, respectively, when compared to the uncontrolled response. Conclusion It is found that in all subcases analyzed the developed optimization framework successfully found the best response of the antenna using the utopian point method. These results confirm the effectiveness of the proposed method.